2021
DOI: 10.11591/ijeecs.v24.i1.pp581-589
|View full text |Cite
|
Sign up to set email alerts
|

Digital agriculture based on big data analytics: a focus on predictive irrigation for smart farming in Morocco

Abstract: Due to the spead of objects connected to the internet and objects connected to each other, agriculture nowadays knows a huge volume of data exchanged called big data. Therefore, this paper discusses connected agriculture or agriculture 4.0 instead of a traditional one. As irrigation is one of the foremost challenges in agriculture, it is also moved from manual watering towards smart watering based on big data analytics where the farmer can water crops regularly and without wastage even remotely. The method use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…In recent years, several effective studies have shown that there is a rapid and high demand for water [2], [3]. We have also noticed that there has been an intense shift from traditional irrigation to smart irrigation based on Internet of Things technology to fully automate and remotely examine water requirements [4], [5]. In this axis, an interesting study based on the internet of things and image processing was developed, in this study, the researchers hoped that this intelligent system will improve the method of breeding Phalaenopsis in the future [6].…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, several effective studies have shown that there is a rapid and high demand for water [2], [3]. We have also noticed that there has been an intense shift from traditional irrigation to smart irrigation based on Internet of Things technology to fully automate and remotely examine water requirements [4], [5]. In this axis, an interesting study based on the internet of things and image processing was developed, in this study, the researchers hoped that this intelligent system will improve the method of breeding Phalaenopsis in the future [6].…”
Section: Related Workmentioning
confidence: 99%
“…Topic Solution [58] Irrigation Management [59], [61]- [66] Irrigation System [60] Irrigation Control [67] Irrigation Timing Decision [68] Irrigation Predictive…”
Section: Referencesmentioning
confidence: 99%
“…SVMs were initially intended for linear models but non-linear ones can be made by transforming input X through a non-linear mapping Φ(X) and then applying conventional linear SVMs over features Φ(X). According to the data, the performance of SVM is the same order, or even better, than a neural network (NN) [25].…”
Section: Support Vector Machine (Svm) Algorithmmentioning
confidence: 99%